Pencegahan Stunting Dapat Dilakukan Ibu yang Mempunyai Balita Dengan Memiliki Pengetahuan yang Baik Tentang Status Gizi Anak Di Puskesmas Lubuk Buaya Padang Tahun 2024 - Eka Seba Marta (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2024)
Stuntingis definedascondition where thenutrional status of children TB/U results Z -score +<-2 SD growth failure. to prevent stunting at the Lubuk Buaya Community Health Center, Padang. This descriptive analytical research uses a cross- sectional study design, conducted at the Lubuk Buaya Community Health Center fromApril to August 2024.The samplingte chniqueu sedwas accidental sampling with 0res pondents. The results showed that 60% of respondents had poor stunting prevention efforts, 46.7% had low knowledgehad a negative attitude towards stunting prevention. There is a significant relationship between the knowledge and attitudes of mothers and efforts to prevent stunting. Keywords:Knowledge, Stunting